Cell adhesion molecules and eNOS expression in aorta of normocholesterolemic mice with different predispositions to atherosclerosis - Rathouska, Jana; Nemeckova, Ivana; Zemankova, Lenka; Strasky, Zbynek; Jezkova, Katerina; Varejckova, Michala; Nachtigal, Petr (Heart and vessels, 2015)
C57BL/6J (B6) mice were demonstrated to be the most susceptible and C3H/HeJ (C3H) mice the most resistant to development of atherosclerosis. We hypothesized, whether pro-atherogenic (P-selectin, VCAM-1, and ICAM-1) and anti-atherogenic (endoglin and eNOS) proteins are expressed differently in aorta before the onset of atherosclerosis in these two mouse strains. B6 mice (n = 16) and C3H mice (n = 16) sustained on either chow or cholesterol (1 %) diet for 8 weeks. Biochemical analysis of lipoprotein profile and Western blot analysis of P-selectin, VCAM-1, ICAM-1, eNOS, endoglin, peNOS and TGF-βRII in aorta were performed. Western blot analysis revealed a lower expression of P-selectin by 7 %, VCAM-1 by 51 %, ICAM-1 by 6 %, and a higher expression of eNOS (by 18 %) in C3H mice in comparison with B6 mice after cholesterol diet. Further analysis revealed that cholesterol diet significantly increased the expression of endoglin (by 97 %), TGF-βRII (by 50 %), eNOS (by 21 %) and peNOS (by 122 %) in C3H mice, but not in B6 mice. We propose that lower expression of P-selectin, VCAM-1 and ICAM-1 and higher expression of eNOS in vivo in aorta of C3H mice might represent another potential mechanism for C3H mice being less susceptible to atherosclerosis when compared to B6 mice. In addition, endoglin seems to be involved in an upregulation of eNOS only in C3H mice. Thus, we propose that aorta of C3H mice is less prone to the expression of pro-inflammatory and endothelial dysfunction markers when compared to B6 mice, regardless of lipoprotein profile and before any signs of atherosclerotic process.
Keywords: ochranné faktory; genetická predispozice k nemoci; Cell Adhesion Molecules; Inflammation Mediators; aorta; Nitric Oxide Synthase Type III; Mice, Inbred C3H; Species Specificity; mediátory zánětu; Atherosclerosis; Animals; myši inbrední C57BL; ateroskleróza; Protective Factors; Phenotype; zvířata; rizikové faktory; myši inbrední C3H; fenotyp; molekuly buněčné adheze; Genetic Predisposition to Disease; Mice, Inbred C57BL; Aorta; synthasa oxidu dusnatého, typ III; ženské pohlaví; Female; druhová specificita; Risk Factors